1999
DOI: 10.1364/josaa.16.002169
|View full text |Cite
|
Sign up to set email alerts
|

Independent-component analysis of skin color image

Abstract: The spatial distributions of melanin and hemoglobin in human skin are separated by independent-component analysis of a skin color image. The analysis is based on the skin color model with three assumptions: (1) Spatial variation of color in the skin is caused by two pigments, melanin and hemoglobin; (2) the quantities of the two pigments are mutually independent spatially; and (3) linearity holds among the quantities and the observed color signals in the optical density domain. The results of the separation ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
114
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(115 citation statements)
references
References 9 publications
0
114
0
1
Order By: Relevance
“…3) The observed color signals and the quantities of them keep the linearity in the optical density domain. Tsumura et al [9] extracted components of hemoglobin and melanin from a human skin color image by using an ICA algorithm. Based on the linearity assumption, the skin color model in the optical density domain of RGB channels can be expressed by the color den- are relative quantities of two pigments.…”
Section: Skin Decompositionmentioning
confidence: 99%
“…3) The observed color signals and the quantities of them keep the linearity in the optical density domain. Tsumura et al [9] extracted components of hemoglobin and melanin from a human skin color image by using an ICA algorithm. Based on the linearity assumption, the skin color model in the optical density domain of RGB channels can be expressed by the color den- are relative quantities of two pigments.…”
Section: Skin Decompositionmentioning
confidence: 99%
“…Tsumura et al first suggested using a simple Lambert-Beer type of law for radiance from a multilayer skin surface, resulting from illumination by polarized light [5]. That is, employing a model similar to a simple logarithm model based on optical densities for accounting for light passing for example through multilayer slide film.…”
Section: Colour Space Image Formulationmentioning
confidence: 99%
“…Tsumura et al (1999) applied the independent component analysis method to the pixel values of color images of faces and also extracted two independent color components corresponding to melanin and hemoglobin. These are indeed located in two different layers of the skin.…”
Section: State Of the Artmentioning
confidence: 99%